Fluktuasi Harga Minyak Gaharu: Analisis Lintas Negara Produsen Minyak Gaharu di Asia - Andrew Stevie Siswanto; Erwindo Sutanto; Fadel Ikhsan Fahaby; Siska Merrinda; Theodorus Zico Utomo Lili (Universitas Prasetiya Mulya, 2018)
Natural oud oil is one of commodities with high demand but the supply is very limited. The price of global oud oil is tended to be fluctuative and unpredictable. This journal will examine the relativity between export selling price within cross country in South East Asia and East Asia with average of global oud oil selling price. The analysis to assess correlation cross country price is using regression analysis model. Further more this research objective is also to compare the movement of oud oil price from exporter country which has dominant impact to Indonesia oud oil price movement. Result of this research analysis is to estimate the oud oil pricing method and to get the most affective guidance or reference of oud oil price as one of the commodities in Indonesia to be able to compete in global market. Keywords: Oud Oil, Regression Analysis, Cross Country Analysis, Price Fluctuation